2022
DOI: 10.1161/strokeaha.122.039579
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants Versus Vitamin K Antagonists in Cerebral Venous Thrombosis: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: High level evidence for direct oral anticoagulants (DOACs) in patients with cerebral venous thrombosis is lacking. We performed a systematic review and meta-analysis to assess the efficacy and safety of DOACs versus vitamin K antagonists in patients with cerebral venous thrombosis. METHODS: This systematic review was registered in PROSPERO (CRD42021228800). We searched MEDLINE (via Ovid), EMBASE, CINAHL, and the Web of Science Core Collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 45 publications
(88 reference statements)
3
26
0
Order By: Relevance
“…Many (68.2%) used DOAC in treatment of CVT. 26 Dabigatran (42.9%) was the most commonly used followed by Apixaban (14.3%) and Rivaroxaban (11.6%). One-third used prophylactic anti-epileptics in treatment of CVT.…”
Section: Discussionmentioning
confidence: 99%
“…Many (68.2%) used DOAC in treatment of CVT. 26 Dabigatran (42.9%) was the most commonly used followed by Apixaban (14.3%) and Rivaroxaban (11.6%). One-third used prophylactic anti-epileptics in treatment of CVT.…”
Section: Discussionmentioning
confidence: 99%
“…It found that direct oral anticoagulant treatment was associated with a similar rate of recurrent venous thromboembolism (5.26 versus 5.87 per 100 patient years), a lower risk of major hemorrhage (2.44 versus 4.70 per 100 patient years), and similar rates of death and recanalization as with vitamin K antagonists. 94 In ACTION-CVT, two-thirds of patients on direct oral anticoagulants were treated with apixaban. Although ACTION-CVT and other retrospective treatment studies are prone to confounding by indication, no major safety issues have been found with the use of direct oral anticoagulants as opposed to vitamin K antagonists in clinical practice.…”
Section: Duration Of Anticoagulationmentioning
confidence: 99%
“…77 For longer-term treatment in stable patients, the tendency is toward the use of novel oral anticoagulants after the RE-SPECT CVT (A Clinical Trial Comparing Efficacy and Safety of Dabigatran Etexilate With Warfarin in Patients With Cerebral Venous and Dural Sinus Thrombosis) trial (randomized 1:1 dabigatran versus dose-adjusted warfarin) showed no significant differences in efficacy and safety, and the retrospective ACTION CVT (Direct Oral Anticoagulants Versus Warfarin in the Treatment of Cerebral Venous Thrombosis) showed that novel oral anticoagulants and warfarin had similar clinical and radiographic outcomes. 78,79 Considerations for anticoagulant choice during pregnancy and lactation, as well as the effects of anticoagulant choice on fertility, are included in TABLE 4-11. 80 For women with a history of CVT, prophylaxis with low-molecular-weight heparin during future pregnancies and postpartum periods is reasonable.…”
Section: Commentmentioning
confidence: 99%